The status and distribution of a newly identified endemic galaxiid in the eastern Cape Fold Ecoregion, of South Africa. Issue 1 (17th November 2017) - Chakona, Gamuchirai; Swartz, Ernst R.; Chakona, Albert
Abstract: DNA‐based studies have uncovered cryptic species and lineages within almost all freshwater fishes studied thus far from the Cape Fold Ecoregion (CFE) of South Africa. These studies have changed the way the CFE is viewed, as almost all stream fishes that were previously considered to be of low conservation priority, because they were perceived to have broad geographical ranges, contain multiple historically isolated lineages, many of which are narrow‐range endemics. As stream fishes of the CFE are of conservation concern owing to threats mainly posed by habitat degradation, invasion by alien species and hydrological modification, re‐evaluation of the distribution and conservation status of newly identified unique lineages is required to inform the development and implementation of effective conservation and management strategies. The present study conducted an IUCN Red List conservation assessment of a newly identified lineage of the Galaxias zebratus species complex (hereafter referred to as Galaxias sp. 'Joubertina') to identify key threats and provide recommendations to conservation authorities on appropriate measures to reduce extinction risk. The lineage met the qualifying threshold for the Endangered category because of its very restricted geographic range, few remaining secure populations, small known population sizes and the intensity of threats to most of the populations. Only six populations remain, one of which could be an 'extralimital' population potentially established through an inter‐basin water transfer scheme. Galaxias sp. 'Joubertina' is threatened by invasive piscivores, habitat degradation and excessive water abstraction. These impacts have fragmented remnant populations, raising concerns about potential long‐term adverse impacts on genetic diversity and evolutionary potential of this lineage. Immediate conservation measures should protect remnant populations from further impacts, while long‐term measures should aim to restore historical connectivity to reduce the potential deleterious effects of inbreeding in the small isolated populations.